2021
DOI: 10.1016/j.bioactmat.2020.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the inflammatory cycle by a controllable release hydrogel for eliminating postoperative inflammation after discectomy

Abstract: Surgery is the final choice for most patients with intervertebral disc degeneration (IDD). Operation-caused trauma will cause inflammation in the intervertebral disc. Serious inflammation will cause tissue defects and induce tissue degeneration, IDD recurrence and the occurrence of other diseases. Therefore, we proposed a scheme to treat recurrence after discectomy by inhibiting inflammation with an aspirin (ASP)-loaded hydrogel to restore the mechanical stability of the spine and relieve local inflammation. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 49 publications
(59 reference statements)
0
39
0
Order By: Relevance
“…Here we review recent advances in modulating ECM homeostasis for the treatment of IDD (Table 1). TA-functionalized polymer capsules Downregulate MMP-3 and ADAMTS-5 [119] Aspirin controllable release hydrogel Downregulate MMP-3/13 and ADAMTS-4/5 [120] Injectable microspheres load with TNFRII or APETx2 Downregulate MMP-3 and ADAMTS-5 via modulate local inflammation microenvironment [121,122] Gene therapy AAV2-TIMP1 promote synthesis of type II collagen [123] TGF-β3, CTGF and TIMP1 co-transduction Promote synthesis of aggrecan and type II collagen [124] ADAMTS-5 siRNA Downregulate ADAMTS-5 [125] PRP: Platelet-Rich Plasma, DHP: 1,4-dihydropyridine, TIMP-1: tissue inhibitor of metalloproteinase 1, CCL-5: C-C motif chemokine ligand 5, ALN: alendronate, TNFRII: tumor necrosis factor receptor type II. TGF-β3: transforming growth factor, CTGF: connective tissue growth factor, ADAMTS: A disintegrin and metalloprotease with thrombospondin motifs, MMP: Matrix metalloproteinase.…”
Section: Therapeutic Targeting Of Proteases For Idmentioning
confidence: 99%
“…Here we review recent advances in modulating ECM homeostasis for the treatment of IDD (Table 1). TA-functionalized polymer capsules Downregulate MMP-3 and ADAMTS-5 [119] Aspirin controllable release hydrogel Downregulate MMP-3/13 and ADAMTS-4/5 [120] Injectable microspheres load with TNFRII or APETx2 Downregulate MMP-3 and ADAMTS-5 via modulate local inflammation microenvironment [121,122] Gene therapy AAV2-TIMP1 promote synthesis of type II collagen [123] TGF-β3, CTGF and TIMP1 co-transduction Promote synthesis of aggrecan and type II collagen [124] ADAMTS-5 siRNA Downregulate ADAMTS-5 [125] PRP: Platelet-Rich Plasma, DHP: 1,4-dihydropyridine, TIMP-1: tissue inhibitor of metalloproteinase 1, CCL-5: C-C motif chemokine ligand 5, ALN: alendronate, TNFRII: tumor necrosis factor receptor type II. TGF-β3: transforming growth factor, CTGF: connective tissue growth factor, ADAMTS: A disintegrin and metalloprotease with thrombospondin motifs, MMP: Matrix metalloproteinase.…”
Section: Therapeutic Targeting Of Proteases For Idmentioning
confidence: 99%
“…Inflammation and oxidative stress are thought to play important roles in disc degeneration [4,5]. Most previous studies showed that IDD was a passive process: the local homeostasis of intervertebral disc (IVD) tissues was destroyed, the biomechanical relationship of normal lumbar vertebrae was changed, and the number of local inflammatory cells and the secretion and synthesis of related inflammatory factors were altered [4,[6][7][8][9][10][11]. The significantly high expression of inflammatory factors is an important characteristic of the inflammatory microenvironment of the degenerative nucleus pulposus.…”
Section: Introductionmentioning
confidence: 99%
“…But there are still many problems between the microenvironment and transplanted cells. Although some ROS serve as signaling molecules in cells, excessive oxidative and inflammation production is harmful and has been implicated in progression of IVDD [ 46 ]. ROS production and nonspecific inflammation generated during the IVDD pathological process have been demonstrated in leading to loss of transplanted stem cells.…”
Section: Discussionmentioning
confidence: 99%